Mono- and multimeric ferrocene congeners of quinoline-based polyamines as potential antiparasitics. Issue 34 (3rd August 2016) - Stringer, Tameryn; De Kock, Carmen; Guzgay, Hajira; Okombo, John; Liu, Jenny; Kanetake, Sierra; Kim, Jihwan; Tam, Christina; Cheng, Luisa W.; Smith, Peter J.; Hendricks, Denver T.; Land, Kirkwood M.; et al.
Abstract : A series of mono- and multimeric polyamine-containing ferrocenyl complexes bearing a quinoline motif were prepared. Abstract : A series of mono- and multimeric polyamine-containing ferrocenyl complexes containing a quinoline motif were prepared. The complexes were characterised by standard techniques. The molecular structure of the monomeric salicylaldimine derivative was elucidated using single crystal X-ray diffraction and was consistent with the proposed structure. The antiplasmodial activity of the compounds were evaluated in vitro against both the NF54 (chloroquine-sensitive) and K1 (chloroquine-resistant) strains of Plasmodium falciparum . The polyamine derivatives exhibit good resistance index values suggesting that these systems are beneficial in overcoming the resistance experienced by chloroquine. Mechanistic studies suggest that haemozoin formation may be the target of these quinoline complexes in the parasite. Some of the complexes exhibit moderate to high cytotoxicity against WHCO1 oesophageal cancer cells in vitro . The monomeric ferrocenyl-amine complexes exhibit potent activity against this particular cell line. The complexes were also screened against the G3 strain of Trichomonas vaginalis and the salicylaldimine complexes demonstrated promising activity at the tested concentration. All of these compounds show no inhibitory effect on several common normal flora bacteria, indicative of their selectivity for eukaryotic pathogens and cancer.